Drop-on-demand metal additive manufacturing from droplet formation to 3D structures - Gilani, Negar (2023)
Additive Manufacturing (AM) sits at the forefront of technologies that offer unprecedented capabilities to lead a new industrial revolution. The higher degrees of complexity and flexibility in manufacturing intricate structures whilst maintaining accuracy and precision is one of the key selling points of AM technologies. Drop-on-demand metal jetting (DoD-MJ) is a promising additive manufacturing technique, gaining interest for its direct high-resolution printing of complex single and multi-material components. It also has key advantages over other metal AM techniques, such as avoiding powder handling and extensive post-processing. DoD-MJ processes are categorised based on the droplet generation actuation method. MagnetoHydroDynamic (MHD) actuators are the most advanced devices to date that have overcome the challenges of producing high-temperature droplets at high rates. MetalJet, the MHD-based system used in this thesis, has the capacity to produce molten micro-droplets (60–90 μm) at temperatures up to 2000 °C to form single and multi-material objects at 500 Hz. Applications for this technology include flexible circuits, advanced electronic components, intricate 3D mesoscale objects, and biotechnologies. In this method, 3D parts are built via spatially controlled deposition of individual molten droplets onto a substrate. Therefore, the success of the process entirely depends on the behaviour of these single droplets from deposition to solidification. Owing to its novelty, further utilization of this technology is impeded to date by a lack of understanding of various aspects of the process, including droplet generation and interface formation, residual stress development and microstructure evolution, which have been scarcely investigated to date. This thesis uses an integrated numerical, experimental, and analytical approach to provide insights into these research questions. The in-house MetalJet platform was used to investigate formation, spreading, and solidification of metallic micro-droplets at low Weber numbers. This was undertaken by ejection and deposition of single and multiple droplets of low (Sn) and high-temperature (Ag and Cu) metal onto various substrates using a range of jetting and substrate temperatures. High-speed photography provided insight into the mechanism of droplet generation. Analytical modelling based on the scaling method was performed to investigate the dynamics of droplets on deposition. Thermal Finite Element (FE) models were used alongside to explain the experimentally-observed morphology of droplets and investigate the droplet-to-substrate and droplet-droplet adhesion. Moreover, thermo-mechanical FE modelling was used to study the residual stress evolution during the solidification and cooling processes, and investigate its role in the observed droplet warping and delamination. Furthermore, various characterisation techniques, including FIB-SEM, EDX, EBSD, and TEM, were used to evaluate the microstructure of printed droplets. For the first time, the generation mechanism of uniform microdroplets at high temperatures and the role of jetting voltages are explained in this thesis. Moreover, this study reports that increasing the substrate temperature intensified the diffusion between the droplet and substrate, which resulted in improved adhesion. It is also shown that ripples forming on a droplet’s periphery during solidification disappeared at elevated substrate temperatures, resulting in enhanced inter-droplet bonding. Furthermore, the significant role of the substrate wettability and thermal properties, which control the droplet’s dynamics and solidification behaviour, respectively, is elucidated. This highlights the importance of the substrate material selection for this technology. It is demonstrated that the steep temperature gradients during deposition result in residual stresses, and if they exceed the elastic limits of the material, stress-induced delaminating can occur. Finally, results presented in this thesis underpin the optimal process conditions under which the 3D structures produced with this technology can exhibit reliable integrity and consistency. Overall, the works represent a step forward towards the direct metal printing of high-resolution functional multi-material components.